A common representation for semantic and physical properties: a cognitive-anatomical approach. - Cohen Kadosh, R; Henik, A (2006)
This is the first report of a mutual interference between luminance and numerical value in magnitude judgments. Instead of manipulating the physical size of compared numbers, which is the traditional approach in size congruity studies, luminance levels were manipulated. The results yielded the classical congruity effect. Participants took more time to process numerically larger numbers when they were brighter than when they were darker, and more time to process a darker number when its numerical value was smaller than when it was larger. On the basis of neurophysiological studies of magnitude comparison and interference between semantic and physical information, it is proposed that the processing of semantic and physical magnitude information is carried out by a shared brain structure. It is suggested that this brain area, the left intraparietal sulcus, subserves various comparison processes by representing various quantities on an amodal magnitude scale.